Make-up, hair and costume for film and television - Musgrove, Jan (Media manuals., 2013)
An introductory guide for students learning professional make-up, hairdressing and wardrobe skills and `front of camera' professionals needing an understanding of the techniques. Written by an experienced professional, this manual offers a step-by step approach for the complete beginner with diagrams to show procedures for a variety of make-up effects, from corrective and character make-up, to period dramas, special effects and prosthetics. It describes the skills required of the job, introduces special make-up products and how to apply them for different effect and sets the context for the make-up artist's role, by considering technical requirements such as lighting, camerawork and chroma-key backgrounds.